Предмет: Алгебра,
автор: marko4489
помогите пожалуйста решить примеры
Приложения:
Ответы
Автор ответа:
0
Объяснение:
27^(-1) ×81^2 ×(3^(-3))^3 ÷81^(-3)=9^4
3^(-3) ×3^8 ×3^(-9) ÷3^(-12)=3^8
3^(-3+8-9+12)=3^8
3^8=3^8
7^(-2) ×21^2 ×(6^-3)^2 ÷14^(-3) ÷343=2^(-3) ×9^(-2)
7^(-2) ×(7×3)^2 ×(3×2)^(-6) ÷(7×2)^(-3) ÷7^3=2^(-3) ×3^(-4)
7^(-2+2+3-3) ×3^(2-6) ×2^(-6+3)=2^(-3) ×3^(-4)
7^0 ×3^(-4) ×2^(-3)=2^(-3) ×3^(-4)
3^(-4) ×2^(-3)=2^(-3) ×3^(-4)
4^(-1) ×8^2 ×(а^-3)^3 ÷(8а^(-3))^2=0,25а^(-3)
4^(-1) ×8^(2-2) ×а^(-9+6)=0,25а^(-3)
1/4 ×8^0 ×а^(-3)=0,25а^(-3)
0,25а^(-3)=0,25а^(-3)
a^(-1) ×(ab)^2 ×(b^(-3))^3 ÷b^(-3)=ab^(-4)
a^(-1+2) ×b^(2-9+3)=ab^(-4)
ab^(-4)=ab^(-4)
Похожие вопросы
Предмет: Физика,
автор: zobninapd
Предмет: История,
автор: nastyu101
Предмет: История,
автор: mgrzhnty
Предмет: Литература,
автор: elizavetkapavl2
Предмет: Литература,
автор: kateshpak